Psychological Distress Among Healthcare Professionals During the Early Stages of the COVID-19 Outbreak in Low Resource Settings: A Cross-Sectional Study in Bangladesh - Md. Riad Hossain (Frontiers Media S.A., 2021)
The COVID-19 pandemic has been very destructive to and compromised the functioning of all nations' public health systems. In the absence of a vaccine, healthcare workers have been employed to relentlessly fight against COVID-19. The psychological status of healthcare workers during the pandemic in countries with limited resources, notably Bangladesh, remains unclear. The present study aimed to investigate the psychological states of frontline and non-frontline Bangladeshi healthcare workers during the early stages of the COVID-19 outbreak. An online cross-sectional study was conducted from May 5 to 31, 2020 with 203 respondents. Psychological states were measured with a self-reported numerical scale of fear, the Generalized Anxiety Disorder (GAD-7) scale, and the Patient Health Questionnaire (PHQ-9). The prevalence rates of fear, anxiety, and depression were 60.6, 71.9, and 55.2%, respectively. Compared to non-frontline workers, frontline workers reported higher rates of anxiety (79.0 vs. 67.2%) and depression (65.4 vs. 48.4%). Multivariate logistic regression models showed that working in a public institution, being employed for <5 years, and being over-worked were risk factors for developing psychological distress. Our findings emphasize the need for timely psychological interventions to support the mental well-being of healthcare professionals in Bangladesh.